Access and use of agricultural market information by smallholder farmers: Measuring informational capabilities. Issue 6 (3rd April 2020) - Magesa, Mawazo M.; Michael, Kisangiri; Ko, Jesuk
Abstract: While farmers sell their crops, middlemen provide a linkage between them, markets and buyers. Middlemen have good knowledge of working conditions of markets and have access to agricultural market information. Due to poor access to markets and agricultural market information by smallholders, there is a feeling that middlemen benefit more while farmers sell their crops. Good access to markets and market information may help farmers bypass middlemen while selling crops and thus benefit more. Thus, it is best to improve the informational capabilities (ICs) of farmers in agricultural marketing. Thus, this research measured ICs of farmers accessing market information, through a program NINAYO, while selling their crops. The research utilized the informational, psychological, social, and economic dimensions of the empowerment framework in identifying capability indicators to formulate survey questions. Data were collected from smallholders in six regions in Tanzania. The analysis utilized measures of life satisfaction and results showed that about half of the variation in the dependent variable, satisfaction with capabilities, was explained by the model. Backward elimination analysis confirmed that life satisfaction is multidimensional. Robustness test confirmed a positive relationship between satisfaction and capabilities. Overall, results confirmed ICs are multidimensions, their improvement empowers farmers in agricultural marketing.